Cyber Law and Cyber Security Policies in Pakistan: A Comparative Study with USA, Canada and Australia - Watto, Omer Mahmood; Islam, Muhammad; Hussain, Syed Arshad; Shahab, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
This study evaluates cyber-law and security policies in Pakistan, the USA, Canada, and Australia, exploring how each country's geopolitical and socioeconomic context influences its cyber-defense and lawful measures against cyber threats. It compares their policies to find out best practices and gaps, aiming to guide the creation of stronger, more adaptable cyber-policies. The research emphasizes the importance of comprehensive legal frameworks to protect against emerging cyber threats and the vital role of international collaboration in enhancing global cyber resilience.